The twelve clues of Christmas [large type] - Bowen, Rhys (Bowen, Rhys. Royal Spyness mysteries., 2012)
While serving as an assistant to the hostess of a large Christmas house party in Tiddleton-under-Lovey, Georgie gets the attention of her retired detective grandfather after dead bodies begin showing up.